A train covers a certain distance at a uniform speed. If the train had been 6 km/hr faster, it would have taken four hours less than the scheduled time. And if the train were slower by 6 km/hr, the train would have taken six hours more than the scheduled time. Find the length of the journey in kilometers.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
we know that speed= dist/time let x be the speed and y be the time taken then we get, Dist= xy from 1 condition, (x+6)(y-4)= xy, therefore,we get , -4x+6y=24 as per 2 condition , (x-6)(y=6)= xy therefore,we get , 6x-6y = 36 now adding these 2 equations we get, x = 30 now substituting x= 30 in any of these two equations weget, y= 24 since , speed= dist/time,then dist =xy=(30)(24)=720 km
where did you get t-4? how it's happened? kindly elaborate.. thanks..
The t − 4 comes from the fact that when the rate is 6 kph more, r + 6 , we are given that it takes 4 hours less, t − 4 . The same logic is applied to the other part of the equation.
how you cancel out the (rt)...
There is two (rt) each one in each side of the equasion, so u just cancel.
Solution:
Let the length of the journey be d km and the speed of train be S km/hr.
Then, d (S+6) =t−4 -------- (i) and d (S−6) =t+6 --------- (ii)
Subtracting the 1 equation from another we get: d (S−6) − d (S+6) =10 -------- (iii)
Now , t= d S
Substitute in equation (i) and solve for d and S We get S=30
Let,
d - length of the journey in km,
S - speed of train in km/hr and
t - scheduled time of journey
Then,
( S + 6 ) d = t − 4 -------- (1)
and
( S − 6 ) d = t + 6 --------- (2)
Subtracting the equation (1) from equation(2) we get:
( S − 6 ) d − ( S + 6 ) d = 10 -------- (iii)
Now , t = S d
Substitute in equation (1) and solve for d and S
We get,
S= 3 0 and d= 7 2 0
Hence, the total distance of journey is 7 2 0 k m
best solution ever,, please become friend man
lets say distance covered=x, velocity=v, tome taken =t, therfore x=v t, from the given conditions: x=(v+6) (t-4), x=(v-6) (t+6), on solving we get 6t-4v=24 and 12t-10v=-12. on solving we get v=30 and t=24 tgherfore x=24 30=720
Neat
easy way
Understandable.
nice
First of all we need to take out all the posible equation
x/y=k---first equation
next the description mention that x/y-4=k+6,x/y+6=k-6
so we solve the equation and we got
x=ky-4k+6y-24and x=ky+6k-6y-36
then we substitute the equation and we got 2k=60,k=30 6y=6(30)-36 y=30-6 y=24
from the first equation x=ky x=24*30=720
Let the initial speed be "x", and the length of the journey be "y". The initial time is y/x. Given: (x+6)(y/x-4)=y. Thus- y-4x+6y/x-24=y ; y=2/3*x^2+4x
Given: (x-6)(y/x+6)=y ; (x-6)((2/3 x^2+4x)/x+6)=2/3 x^2+4x 2/3 x^2+4x+6x-4x-24-36= 2/3 x^2+4x 2x-60=0 2x=60 x=30
y(journey)= 2/3 30^2+4 30= 600+120= 720
Let the uniform speed be s and the time takes(in hours) to be t, Then, Distance traveled will be s t. It has been given that if the speed is 6 more than the regular speed then the time taken is 4 hours less than the regular time. This means that if the speed is s+6 then the time is t-4. Since, Distance=Speed Time, S t=(s+6) (t-4)....[This is our first equation...] Similarly, when speed is s-6, the time taken is t+6. So, s t=(s-6) (t+6).....[This is our second equation] When we equate the two equations, we get s=30km/hr and t=24 hours. Thus distance=s t=24 30=720 km
let us take the original velocity of the train be u km/h and total distance travelled be x km so the original time(scheduled time) be t hours.When speed increased by 6km/h then our new speed is (u+6)km/h then the new time of travel is t1=x/(u+6) hrs this time is 4 hr less than sheduled time so we can form an equation: x/u - x/(u+6)=4............(1) similarly if the train travels 6km/h less than the original speed than the new speed is (u-6)km/h so the new time taken t2=x/(u-6) hrs according to the question it takes 6 hour more to travel the same distance so another equation can be formed: x/(u-6) -x/u=6...........(2) so solving equation (1)and(2) first we find u=30km/h and inserting this value in any one of the equation would give x=720 km. (Rather than just doing calculation i tried to focus on the concept i hope every one understand this) :)
Let the length of the journey be d km and the speed of train be S km/hr.
Then, d (S+6) =t−4 -------- (i) and d (S−6) =t+6 --------- (ii)
Subtracting the 1 equation from another we get: d (S−6) − d (S+6) =10 -------- (iii)
Now , t= d S
Substitute in equation (i) and solve for d and S We get S=30 d= 720 km
Lets say Distance= d, Time =t and Velocity=v d=v x t (1) At speed of 6Km/hr faster, time wud have been 4 hrs less so d = (v+6) x (t-4) (2) At speed of 6Km/hr slower, time wud have been 6 hrs more so d=(v-6) x ( t+6) (3) as distance remains the same so equating (1) and (2) we get 6t-4v=24 (4) and equating (1) and (3) we get v-t=6 (5) solving (4) and (5) we get v=30Km/hr and t=24 hrs So as d=v x t d=30 x 24 = 720 Km
let x be scheduled time, y be speed of train
When the train 6km/hr faster than the normal speed, it will 4 hours less than the scheduled time,so (x-4)hr ; (y+6)km/hr
When the train 6km/hr slower than the normal speed, it will 6 hours more than the scheduled time, so (x+6)hr ; (y-6)km/hr
From the question, if the train moves in uniform speed, x, then it reach to the destination on the scheduled time,y, so the distance is x hr * y km/hr=xy km
Since the distance is same, so (x-4)hr * (y+6)km/hr = (x+6)hr * (y-6)km/hr xy+6x-4y-24 = xy-6x+6y-36 6x-5y+6=0 --(i)
xy=xy+6x-4y-24 6x-4y-24=0 --(ii)
(ii) subtract (i) : y-30=0 y = 30 x = 24 distance = x*y = 24 * 30 = 720
xy = xy-6x+6-36 6x-6y+36=0 -- (iii)
(i) subtract (iii) : y-30 = 0 y = 30 Since y have only one value, so the x also have only one value, therefore only have one solution for the distance.
Schedule: speed = v and time = t Faster then schedule: speed = v + 6 and time = t - 4 Slower then schedule: speed = v - 6 and time = t + 6 Total distance = x = speed . time
so we get: v.t=x and (v+6).(t-4)=x and (v-6).(t+6)=x We solve t = 24 and v = 30 Now x = v.t = 30.24 = 720
After all the math on my paper, I saw that there was multiplechoice...
s=vt (uniform speed) …………………………….(i) s=(v+6)(t-4)(condition 1st)……………………….(ii) s=(v-6)(t+6)(condition 2nd)………………………(iii) Solving (ii) & (iii), we get, vt - 4v + 6t – 24 = vt + 6v – 6t – 36 or, 10v – 12t = 12 or, 5v – 6t = 6 ………………………………………..(iv) Solving (i) & (ii), we get, 4v – 6t = -24 …………………………………………….(v) Subtracting (v) from (iv), we get, 5v – 6t - 4v + 6t = 6 +24 Or, v = 30, putting the value of v = 30 in (iv) we get t = 24 then, s = 30 * 24 = 720
let scheduled velocity is: V scheduled time is: T traveled distance: S so, out come is three equation according to the question
S=(V+6)
(T-4)=(V-6)
(T+6)=V
T
so taking (V+6)
(T-4)=V
T we find , 6
V-6
T=36
and taking (V-6)
(T+6)=V
T we find , -4
V+6*T=24
solving these final two equations
we find V=30 and T=24
so S= 720
that's all :-) :-) :-)
x=normal velocity when the train hadn't been faster or slower y=normal time when the train hadn't been faster or slower z= time taken by the train to finish the journey
3 equations:
xy=z
(x+6)(y-4)=z
(x-6)(y+6)=z
solve these 3 equations to get the answer
Let the distance be 'D', Let the speed be 's', Let the time taken be 't' therefore, we know that, D=st ........(1) D=(s+6)(t-4).........(2) D=(s-6)(t+4)..........(3) solve the three equations simultaneously to find the values of 's' and 't' which come out to be s=30 km/hr and t=24 hrs. and hence, D=30*24=720kms.
Problem Loading...
Note Loading...
Set Loading...
We set up an equation to model the situation:
Using d = r t , we find that:
d = ( r + 6 ) ( t − 4 ) = ( r − 6 ) ( t + 6 ) = r t d = r t + 6 t − 4 r − 2 4 = r t − 6 t + 6 r − 3 6 = r t
Cancelling the r t terms we get:
6 t − 4 r − 2 4 = − 6 t + 6 r − 3 6 = 0
Which gives us the two equations 6 t − 4 r − 2 4 = 0 and − 6 t + 6 r − 3 6 = 0 .
Adding the two equations gives us 2 r = 6 0 so r = 3 0 . Subsituting this solution gives us t = 2 4 .
Now we multiply these two (since d = r t ) to get our answer of 7 2 0 .